A Missing Link In Forest Conservation-Case Study From Odisha, India - Paul, Shashi (Indian Forester, 2018)
Odisha state has about one third of its geographical area under forest cover. For administration and management of forests it is divided into divisions and circles. Present study covers Berhampur circle one of the eight forest circles and cover four districts which are divided into seven forest divisions. As per available methodologies the total timber demand ranges from about 5 lakh cum per annum to about 10 lakh cum per annum in the circle. Against this demand, supply from all known sources in the four districts in the study area does not exceed about 5% of total demand. This factor is not being taken care of by any plan or strategy available. There is no roadmap available that how this deficit can be met. For this purpose steps like farm forestry, timber substitutes, plantations outside notified forests should be planned. In addition to this the huge area of forests under the control of revenue department (without any forest management presently) should be put to better use through proper management for realizing its production potential. The local demand of tribal and other poor living near the forests has been given top priority in the Forest Policy of 1988. Analysis of the scenario in two highly forested and tribal population dominated districts (Kandhmal and Gajapati) in the study area shows that present system needs to be revamped to meet the policy requirements. In such areas, an effective system supporting easy availability of timber at reasonable prices has to be put in place. In the absence of such steps perhaps the efforts for conservation of forests are not going to yield the desired results.